The Brothers of Romulus : Fraternal Pietas in Roman Law, Literature, and Society - Bannon, Cynthia J. (Book collections on Project MUSE., 2001)
Stories about brothers were central to Romans' public and poetic myth making, to their experience of family life, and to their ideas about intimacy among men. Through the analysis of literary and legal representations of brothers, Cynthia Bannon attempts to re-create the context and contradictions that shaped Roman ideas about brothers. She draws together expressions of brotherly love and rivalry around an idealized notion of fraternity: fraternal pietas--the traditional Roman virtue that combined affection and duty in kinship. Romans believed that the relationship between brothers was especia.